2019
DOI: 10.1101/858480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomic- and cultivation-based exploration of anaerobic chloroform biotransformation in hypersaline sediments as natural source of chloromethanes

Abstract: AbstractChloroform (CF) is an environmental contaminant that can be naturally formed in various environments ranging from forest soils to salt lakes. Here we investigated CF removal potential in sediments obtained from hypersaline lakes in Western Australia. Reductive dechlorination of CF to dichloromethane (DCM) was observed in enrichment cultures derived from sediments of Lake Strawbridge, which has been reported as a natural source of CF. The lack of CF removal in the abioti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…organohalide respiration; there is a wide literature regarding dehalogenation processes in terms of biochemistry of specific compounds (Dolfing 2000;Fetzner 1998;Olivas et al 2002;Pries et al 1994;Smidt and de Vos 2004;van Pee and Unversucht 2003). There are also studies that show netuptake of chloromethane without evidence of organohalide respiration (Peng et al 2020), and a cometabolic dechlorination has been suggested (Atashgahi et al 2018;Peng et al 2020). However, rates and regulation of dechlorination of bulk Cl org in nature are still rarely quantified although the limited available information suggests rates are high (Montelius et al 2016).…”
Section: Processes Driving Terrestrial CL Cyclingmentioning
confidence: 99%
“…organohalide respiration; there is a wide literature regarding dehalogenation processes in terms of biochemistry of specific compounds (Dolfing 2000;Fetzner 1998;Olivas et al 2002;Pries et al 1994;Smidt and de Vos 2004;van Pee and Unversucht 2003). There are also studies that show netuptake of chloromethane without evidence of organohalide respiration (Peng et al 2020), and a cometabolic dechlorination has been suggested (Atashgahi et al 2018;Peng et al 2020). However, rates and regulation of dechlorination of bulk Cl org in nature are still rarely quantified although the limited available information suggests rates are high (Montelius et al 2016).…”
Section: Processes Driving Terrestrial CL Cyclingmentioning
confidence: 99%
“…The transformation of 2,4-D in our microcosms could likely be due to co-metabolism. Co-metabolic reductive dechlorination mediated by vitamin B12 has been demonstrated for other chlorinated compounds such as chloroform, tetrachloromethane, tetrachloroethene, among others (Gantzer and Wackett 1991 , Workman et al 1997 , Smidt and de Vos 2004 , Guereiro-Barajas and Field 2005 ; Becker and Freedman 2014, Peng et al 2020 ). The genus Clostridium was one of the most dominant groups among all microcosms (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 ), and Clostridium that has been identified before as one of the main genera involved in cometabolic transformation of 2,4-D (Yang et al 2018 ). Furthermore, members of the genus Clostridium are also known for their potential for co-metabolic transformation of chlorinated compounds using enzymes involved in the Wood-Ljungdahl pathway (WLP) (Peng et al 2020 ). Unfortunately, we did not monitor cobalamin, but as mentioned before, we observed 2,4-D transformation, and no enrichment of OHRB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation